2001
DOI: 10.1055/s-2001-11184
|View full text |Cite
|
Sign up to set email alerts
|

Small-Intestinal Endoscopy

Abstract: A small imaging capsule without cables, wires, or external connections has been developed for exploration of the small bowel. This swallowable device is propelled by peristalsis through the intestinal tract, and transmits data to a nearby receiver that captures video images on a regular basis. This technology will soon be available throughout the world, and it promises to revolutionize deep endoscopy of the small bowel. Sonde enteroscopy will be laid to rest forever. There continues to be considerable interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
0
9
0
5
Order By: Relevance
“…In 5 ± 40 % of patients with gastrointestinal bleeding, the under− lying cause remains undetected after upper gastrointestinal en− doscopy and colonoscopy [1,2]. In most of these patients the source of bleeding is in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 5 ± 40 % of patients with gastrointestinal bleeding, the under− lying cause remains undetected after upper gastrointestinal en− doscopy and colonoscopy [1,2]. In most of these patients the source of bleeding is in the small intestine.…”
Section: Introductionmentioning
confidence: 99%
“…
IntroductionIn 5 ± 40 % of patients with gastrointestinal bleeding, the under− lying cause remains undetected after upper gastrointestinal en− doscopy and colonoscopy [1,2]. In most of these patients the source of bleeding is in the small intestine.

Radiological methods of screening the small intestine include small−bowel barium follow−through and abdominal computed tomography with enteroclysis, but the diagnostic value of these methods remains limited in gastrointestinal bleeding of obscure origin.

…”
mentioning
confidence: 99%
“…Evaluation of COGB is still one of the challenges in gastroenterology. It is estimated that in 5% to 10% of patients with COGB, the bleeding source cannot be identified by standard endoscopic techniques (ie, upper endoscopy and colonoscopy) (1,2,12). For the diagnosis of COGB, it is suggested that a second upper endoscopy or "second opinion endoscopy" be performed, due to the high frequency of lesions that are overlooked at the initial endoscopy (1).…”
Section: Discussionmentioning
confidence: 99%
“…in the investigation of chronic obscure gastrointestinal bleeding C hronic obscure gastrointestinal bleeding (COGB) is defined as bleeding of unknown origin that persists or recurs (ie, recurrent or persistent iron deficiency anemia, fecal occult blood testing positivity or visible bleeding) after a negative initial or primary endoscopic evaluation (colonoscopy and upper endoscopy) (1,2). The evaluation of COGB involves a series of increasingly interventional investigations such as repeat esophagogastroduodenoscopy and colonoscopy, push enteroscopy (PE) and small intestinal (SI) x-ray study (eg, enteroclysis), nuclear isotope bleeding scan, Meckel scan, angiography and intraoperative enteroscopy.…”
Section: Reproducibility Of Wireless Capsule Endoscopymentioning
confidence: 99%
“…Sonde enteroscopy allows detection of bleeding lesions which are located beyond the reach of push enteroscopy [Berner et al 1994]. However, because the procedure is very prolonged in duration and cannot perform any more advanced therapies, this modality is no longer utilized in clinical practice [Waye, 2001].…”
Section: Angiographymentioning
confidence: 99%